Analisis Hubungan Kausalitas Inflasi, Ipm, Kemiskinan, Dan Pengangguran Di Provinsi Nusa Tenggara Timur - Sultan; Samsuddin, M. Afdal (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the causal relationship between inflation, Human Development Index (HDI), poverty, and unemployment in East Nusa Tenggara (NTT) Province using the Vector Error Correction Model (VECM) approach. The study uses secondary annual data for the period 2014–2023, interpolated into monthly data. The analysis begins with stationarity testing, followed by the Johansen cointegration test, VECM estimation, and Granger causality, impulse response function (IRF), and variance decomposition (VD) analyses. The results show a long-term relationship among the variables, validating the use of the VECM model. Granger causality indicates that only inflation significantly causes poverty. The IRF results reveal that most variables respond more strongly to their own shocks than to shocks from other variables. The variance decomposition supports this, showing that most variations are explained by internal shocks, except for unemployment, which receives the highest external influence from HDI. These findings highlight the importance of focusing on human development policies to reduce unemployment and ensuring price stability to alleviate poverty in NTT.